Compressive Strength of Palm Oil Waste Lightweight Aggregate Concrete Containing Palm Oil Fuel Ash as Partial Cement Replacement - Muhammad Nazrin Akmal, Ahmad Zawawi; Khairunisa, Muthusamy; Norhaiza, Nordin; Nur Azzimah, Zamri; Nasly, Mohamed Ali (PIBEC 2016, 2016)
The increasing amount of by-product generated by Malaysian palm oil mills namely oil palm shell (OPS), palm oil clinker (POC) and palm oil fuel ash (POFA) which are disposed without any profitable value at dumping site has caused huge land consumption and also pollution to the environment. Thus, this problem has lead towards researcher’s effort towards integrating these by-products in concrete production. Integrating POFA as partial cement replacement, OPS as coarse aggregate and POC as fine aggregate in lightweight aggregate concrete would reduce huge amount of waste disposed at the landfill. This paper addresses the compressive strength of palm oil waste lightweight aggregate concrete containing various percentage of POFA as partial cement replacement. Palm Oil Waste lightweight aggregate concrete mixes were produced by replacing various percentage of POFA ranging from 10, 20, 30, 40 and 50%, respectively by weight of cement. In this investigation, all the specimens were prepared in form of cubes (100 mm x 100 mm x 100 mm) and water cured until the testing age. The compressive strength test was carried out at 7 and 28 days following the procedures in BSEN 12390 – 3. The finding shows that specimen produced using 20% POFA exhibit encouraging result value of compressive strength as compared to control specimen. Incorporation of palm oil wastes as mixing ingredient in lightweight concrete production would reduce the amount of waste disposed thus ensuring ecological balance as well as sustainable environment for future generation.